PERAN SOSIALISASI EMOSI OLEH IBU & AYAH TERHADAP REGULASI EMOSI ANAK USIA DINI - Wandansari, Yettie (EXPERIENTIA : Jurnal Psikologi Indonesia, 2019)
Emotion regulation is a skill that develops rapidly in early childhood. Previous research reported that parents play an important role in the development of children's emotion regulation, especially through emotion socialization. This study aims to examine the effect of emotion socialization by mother and father on children’s emotion regulation. Emotion socialization in this study includes the socialization of emotions through parental expression of emotions, parental response to the expression of negative emotions of children, and parental emotion coaching. Participants were 98 pairs of 4-6 years old kindergarten students and their parents. The measurement used Indonesian version of four instruments, includes Self-Expressiveness in the Family Questionnaire (SEFQ), Coping with Children’s Negative Emotions Scale (CCNES), Subscale Coaching of Maternal Emotional Styles Questionnaire (MESQ), and Emotion Regulation Checklist (ERC). The results of multiple regression analysis showed F value of 2.114 (p=0.043). In conclusion, the socialization of emotions by mother and father through emotional expression, responses to child's emotional expression, and emotion coaching, simultaneously affect child's emotional regulation. The contribution of parental emotion socialization to children’s emotional competence is 16%, while the remaining 84% is influenced by other variables not examined in this study.